2019
DOI: 10.1155/2019/9679731
|View full text |Cite
|
Sign up to set email alerts
|

Antiphotoaging and Antimelanogenic Effects of Penthorum chinense Pursh Ethanol Extract due to Antioxidant- and Autophagy-Inducing Properties

Abstract: Ethnopharmacological Relevance. Penthorum chinense Pursh (Penthoraceae) is a traditional herbal plant that has been used in China for the treatment of jaundice, cholecystitis, edema, and infectious hepatitis. In addition, the Korea Medicinal Plant Dictionary states that Penthorum chinense Pursh can be used to treat contusions and skin bruises by improving blood flow. Recent studies have shown that Penthorum chinense Pursh ethanol extract (Pc-EE) exhibits strong antioxidant effects. In this study, we examined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 39 publications
1
31
0
Order By: Relevance
“…However, PCP-EE has antiapoptotic, antiaging, and anti-inflammatory properties that protect HaCaT cells from UVB radiation or H 2 O 2 lethal-induced oxidative stress and increases the promoter activity of the type 1 collagen gene Col1A1 and decreases the UVB radiation or H 2 O 2 induced oxidative stress induced MMPs, COX-2, IL-6, and hyaluronan [ 12 ], suggesting that the treatment of alcohol liver-induced oxidative stress by autophagy is a novel mechanism [ 102 ], combined with quercetin, and the therapeutic results of resveratrol in alcohol liver suggest that it may regulate autophagy through the core regulator of autophagy; the transcription factor forkhead box protein O3 (FOXO3a) [ 103 ] plays an important role in the pathogenesis of alcohol liver [ 104 ], and there is crosstalk between autophagy and apoptosis; PCP and its active ingredients inhibit the PI3K/AKT pathway through SIRT1 activation [ 105 ] by promoting Bcl-xl, the expression of Bcl2, and caspases proteins to regulate apoptosis, and it has been shown that Bcl-2 protein not only counteracts the activity of proapoptotic proteins to downregulate apoptosis but also interacts with Beclin-1 to prevent autophagy. The results suggest that there is some crosstalk between autophagy and apoptosis, providing a new thought on the mechanism of action of PCP in the treatment of alcohol liver [ 106 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, PCP-EE has antiapoptotic, antiaging, and anti-inflammatory properties that protect HaCaT cells from UVB radiation or H 2 O 2 lethal-induced oxidative stress and increases the promoter activity of the type 1 collagen gene Col1A1 and decreases the UVB radiation or H 2 O 2 induced oxidative stress induced MMPs, COX-2, IL-6, and hyaluronan [ 12 ], suggesting that the treatment of alcohol liver-induced oxidative stress by autophagy is a novel mechanism [ 102 ], combined with quercetin, and the therapeutic results of resveratrol in alcohol liver suggest that it may regulate autophagy through the core regulator of autophagy; the transcription factor forkhead box protein O3 (FOXO3a) [ 103 ] plays an important role in the pathogenesis of alcohol liver [ 104 ], and there is crosstalk between autophagy and apoptosis; PCP and its active ingredients inhibit the PI3K/AKT pathway through SIRT1 activation [ 105 ] by promoting Bcl-xl, the expression of Bcl2, and caspases proteins to regulate apoptosis, and it has been shown that Bcl-2 protein not only counteracts the activity of proapoptotic proteins to downregulate apoptosis but also interacts with Beclin-1 to prevent autophagy. The results suggest that there is some crosstalk between autophagy and apoptosis, providing a new thought on the mechanism of action of PCP in the treatment of alcohol liver [ 106 ].…”
Section: Discussionmentioning
confidence: 99%
“…In China, Penthorum chinense Pursh (PCP) has been used for hundreds of years traditionally with the functions of “promote diuresis and reduce swelling,” “circulation of blood,” “circulation of blood stasis,” and “soothing liver and invigorating spleen,” for alleviating symptoms by excessive intake of alcohol as well as in the treatment of traumatic injury, edema, and liver diseases. Recently, it has a wide range of pharmacological effects, such as antiaging [ 12 ], antioxidant [ 13 ], anti-inflammatory [ 14 ], hypoglycemic [ 15 ], antibacterial [ 12 ], and promoting immune regulation. Modern studies have shown that PCP protects the liver and treats acute viral hepatitis and chronic liver diseases, such as viral hepatitis, alcoholic hepatitis, and other alcohol liver diseases [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many recent studies have shown that autophagy regulates melanin formation [ 16 , 17 , 18 , 19 ]. We conducted a study on plant extracts that regulate melanogenesis through autophagy [ 20 ] and confirmed that Pv-EE induces autophagy. In this paper, we analyzed the regulation of melanogenesis using the ability of Pv-EE to induce autophagy.…”
Section: Introductionmentioning
confidence: 91%
“…Total RNA was then isolated with TRIzol reagent according to the manufacturer's instructions. RT-PCR was performed as described previously [28]. Primers used in this study are listed in Table 1.…”
Section: Analysis Of Mrna Levels By Reverse Transcriptase-polymerasementioning
confidence: 99%